Al Lathif Islamic School Principal Performance Analysis In Balanced Scorecard Perspective - Tubilah Noor, Sri (Devotion : Journal of Research and Community Service, 2022)
This study aims to analyze and assess the performance of principals who have implemented school-based management (SBM). An alternative management system tool to measure the work efficiency of the institution in measuring the performance of Al Lathif Islamic School in the city of Bandung using the Balanced scorecard model. A balanced scorecard is a management tool that translates the vision, mission, and organizational strategy of the Al lathif Islamic School into a set of four perspectives, namely the financial, customer, and internal business processes, as well as learning and growth perspectives. This study uses a quantitative approach with descriptive analysis. Primary data in the form of a questionnaire is used to measure the performance of the financial perspective and the perspective of learning and growth, while the measurement of the performance of the financial perspective and internal business process perspective uses secondary data. Sources of data were obtained from Educators, Education Personnel, Students, and Parents, EDS Documents, The Education Unit Accreditation Instrument (2021), Principal's Annual Work Assessment, School Financial Accountability Reports, and School Alumni Documents. The results showed that the performance of Al Lathif Islamic International School was in the very good category. Based on the financial perspective, obtaining good performance, namely meeting the economic requirements, effectiveness, and efficiency. Based on the perspective of the customer get a very good value by applying five dimensions (tangibility, reliability, responsiveness, assurance, empathy). Based on the internal business process perspective, the measurement results can be shown from the innovation aspect, operation aspect, and alumni service that has shown very good value results. Based on the learning and growth perspective, four indicators, namely the range of employee satisfaction, training, employee loyalty, and employee performance productivity are in the very good category